The Public Understanding of Perlanaan Huta IV Teladan Village Towards Sharia Banking Products - Siregar, Pani Akhiruddin; Pakpahan, Elpianti Sahara (Universitas Siliwangi, 2025)
Introduction to The Problem: Sharia banking has a very important role to build understanding of the benefits of sharia banking products and services because the development of sharia banking cannot be separated from the active role of sharia banking itself in conducting socialization and education to the public.Purpose/Objective Study: The research aims to analyze the significant influence between knowledge, education and religious of Perlanaan Huta IV Village on sharia banking products in the Kota Perdagangan.Design/Methodology/Approach: Research methods with quantitative methods described in multiple linear regression analysis models. Primary data by distributing questionnaires to respondents as a sample from October 2020 to May 2021. Sampling design with simple random sampling technique. Using the Slovin formula, the number of respondents who became a sample was 100 people for further analysis.Findings: Research results: (1) The estimation model shows an R2 value of 0,050 which represents the value of the coefficient of determination. This means that 5% of the dependent variable variation is able to be explained by the independent variable in this model. The remaining 95% is explained by other causes that are not included in the model; 2) Regression models on independent variable simultaneously do not influence the dependent variable; and (3) This research resulted in the output that the knowledge of the community of Perlanaan Huta IV Village has an influence and is significant on sharia banking product in the Kota Perdagangan. However, the education and religious of the community of Perlanaan Huta IV Village did not show an insignificant influence on sharia banking product in the Kota Perdagangan.Paper Type: Research Article.